ROLE AND IMPORTANCE OF PROPHYLACTIC PHYSIOTHERAPY DURING THE POSTNATAL PERIOD - Mihaela-Alina CRISTUŢĂ (Editura Universitatii Transilvania din Brasov, 2019)
This paper aimed to emphasize the role played by prophylactic physiotherapy during the postnatal period, in order to re-educate the troubled functions and to heal the injuries suffered during pregnancy and at birth. The prophylactic physiotherapy intervention during the postpartum period can influence/improve the troubled functions and accelerate the healing of the injuries suffered during pregnancy and after birth.